Surgical Approach to Pigmented Villonodular Synovitis and Synovial Osteochondromatosis in Pathological Expansion of the Popliteus Bursa - Sugita, Takehiko (Arthrosc Tech, 2019)
We orthopaedic surgeons are not familiar with the popliteus bursa. It is defined as the expansion in the synovial membrane of the posterolateral part of the knee that lies between the lateral meniscus and the tendon of the popliteus muscle. The popliteus bursa extends approximately 1 cm distal to the joint line and has 4 borders; the medial border is the peripheral margin of the lateral meniscus, the lateral border is the popliteus tendon, and the superior and inferior borders are formed by 2 fascicles. We very rarely observe cystic lesions that expand more distally, such as pigmented villonodular synovitis (PVNS) and synovial osteochondromatosis. We consider the distally expanded bursa as the pathologic expansion of the popliteus bursa. When this expansion is involved with PVNS, it may be the cause of recurrence of PVNS in the knee joint. Synovial osteochondromatosis in this expansion may cause pain in the posterolateral corner of the knee and may become a source of free bodies in the knee joint. In such conditions, these lesions should be surgically excised. The purpose of this Technical Note is to describe a surgical approach to the pathologic expansion of the popliteus bursa.